HEALTH PROFESSIONALS IN ARMED FORCES AND THEIR CONTINUING PROFESSIONAL DEVELOPMENT (CPD): Continuing Professional Development (CPD) - Safdar, Lt Col Aqeel; Jamal, Shahid; Khan, Muhammad Aslam; Ahmed, Gulnaz (Pakistan Armed Forces Medical Journal, 2010)
Biomedical knowledge is rapidly changing with nearly a million new citations in MEDLINE alone every year. There is currently no structured or systematic Continuing Professional Development (CPD) program for health professionals in the Armed Forces of Pakistan. The overall aim is to develop a system of continually updating our knowledge, skills and attitudes that will promote heightened professionalism, both in peace time and war. All health professionals need to be offered opportunities and facilities for their professional growth. Such systems are already in place all over the world. To achieve these objectives careful regulatory mechanism and implementation strategies have to be instituted. Target populations in the order of priority and dedicated providers have to be identified, trained and motivated. With proper monitoring and facilitation a culture of self improvement can easily be created and propagated. Armed forces can easily take the lead in Pakistan. The ultimate beneficiaries will be the armed forces personnel and their families.